Legal Protection of Customary Law Communities Over Ulayat Land Forests - Katjong, Revie Kurnia; Tuhumury, Harry; Roem, Anwar Moch; Sari, Liani (Universitas Negeri Gorontalo, 2023)
This study aims to analyze the concept of customary land customary law, as well as to examine the protection of indigenous peoples in a customary land forest. The type of research in this writing is a normative juridical research method. The approach used in this study is a Statute Approach and a case approach. The results showed customary forests, sometimes referred to as customary forests, are forests within the territory of customary law communities. To be designated as customary Forest, local customary law communities can apply to the Minister of Environment and Forestry. Customary Forests, before Indonesian law is, protected as the legal protection of customary land. This legal protection is a form of concrete action from the state in implementing the mandate of the Constitution of the Republic of Indonesia Constitution of 1945 contained in Article 18b. Moreover, in this case, the government has issued a decree of the Minister of Environment and Forestry to establish customary forest areas and the rights and obligations of Indigenous Peoples.